Multiplicity: An Explorative Interview Study on Personal Experiences of People with Multiple Selves - Ribáry, Gergő; Lajtai, László; Demetrovics, Zsolt; Maraz, Aniko (Frontiers in Psychology, 2017)
Background and aims: Personality psychology research relies on the notion that humans have a single self that is the result of the individual’s thoughts, feelings and behaviours that can be reliably described (i.e., through traits). People who identify themselves as “multiple” have a system of multiple, or alternative, selves that share the same physical body. This is the first study to explore the phenomenon of multiplicity by assessing the experiences of people who identify themselves as “multiple”. Methods: First, an Internet forum search was performed using the terms “multiplicity” and “multiple system”. Based on that search, people who identified themselves as multiple were contacted. Interviews were conducted by a consultant psychiatrist, which produced six case vignettes. Results: Multiplicity is discussed on Twitter, Tumblr, Google+ and several other personal websites, blogs and forums maintained by multiples. According to the study’s estimates, there are 200–300 individuals who participate in these forums and believe they are multiple. Based on the six interviews, it appears that multiples have several selves who are relatively independent of each other and constitute the personality’s system. Each “resident person”, or self, has their own unique behavioural pattern, which is triggered by different situations. However, multiples are a heterogeneous group in terms of their system organisation, memory functions and control over switching between selves. Conclusions: Multiplicity can be placed along a continuum between identity disturbance and dissociative identity disorder, although most systems function relatively well in everyday life. Further research is needed to explore this phenomenon, especially in terms of the extent to which multiplicity can be regarded as a healthy way of coping.